Effect of Erbium on the Microstructure and Mechanical Properties of Semi‐Solid Al–7Si–0.4Mg Alloy. Issue 3 (12th December 2018) - Qi, Peng; Li, Bolong; Wang, Tongbo; Zhou, Lian; Nie, Zuoren
Abstract : In this paper, semi‐solid Al–7Si–0.4Mg– x erbium(Er) ( x = 0, 0.1, 0.3, 0.5, 0.8 wt%) alloys are fabricated via electromagnetic stirring method. The effects of Er on the microstructures and mechanical properties of semi‐solid Al–7Si–0.4Mg alloys are investigated. Results show that the eutectic π‐phase is modified to fine sized Er‐poor π‐phase and primary α‐Al is refined in semi‐solid Al–7Si–0.4Mg alloys with the addition of Er. Meanwhile, the plate‐like shape eutectic Si is transformed into fibrous eutectic Si with addition of Er, which has an excellent modification effect on the eutectic Si. Nucleation rate of the Er‐poor π‐phase is increased with a higher super cooling rate, which causes the refinement of primary α‐Al and the modification of eutectic Si phase. With the addition of 0.3 wt% Er, semi‐solid Al–7Si–0.4Mg alloys obtain the best tensile properties. The ultimate tensile strength and elongation values are 228 MPa and 10.4%, which is increased by 7% and 50% than Er‐free alloy, respectively. Abstract : With the addition of Er into semi‐solid Al–7Si–0.4Mg alloys, the Chinese script π ‐Fe phase is modified to fine size and globule Er‐poor π ‐phase. The addition of 0.3% Er to semi‐solid Al–7Si–0.4Mg alloy improves the tensile strength about 7%, especially elongation (50%), which is attributed to the combined action of eutectic Si modification, primary α ‐Al grain refinement, and π ‐phase modification.